Resocialization in the total institution for education. Reality or utopia? (Research, Society and Development, 2021)
This present article is due to a qualitative study on respect to ressocialization, as a way to recover the detents in a prisional system. It questions if the public policies and the education have an effecttive cooperation to help them. It has also as an object the search of the reality of the actual system of ressocialization. It checks if the ressocialization as the present model is fullfilling with these pragmatical function or it might be done through education.  Nevertheless, what kind of education or pedagogy?  This search follows a methodological study of cases, as presented by Creswell (2014). It also used the phenomenology of Merleau-Ponty (2018). To that purpose, it has been adopted interwies semistructures as a tecnique to obtain informations with the detentions. Others political, legal and educational directions can be considered on thar emerging process for education. The study can also brings results based on social criminology to identify necessities to be taken into account as it moves to innovation and changes into this complex system. This proposal trends to suggest public policies and a social pedagogical education, as much as to produce a new pedagogical view to see what is education.  It will consider first of all the necessity of a new model of education and people prepared for that. They must be ready to develop their commitement to a social view. An educational proposal based on the aim of ressocialization as a reality and a cultural-ambiance emancipation. Something that inspires a complex thought and equality, as Freire perspective.